Drosophila AHR limits tumor growth and stem cell proliferation in the intestine [version 2; peer review: 2 approved, 2 approved with reservations] - Brigitta Stockinger; Jean-Paul Vincent; Alex P. Gould; Nicola Laura Diny; Jiawei Sun; Minghua Tsai; Michael Shapiro; Cyrille Alexandre; Ying Li; Adrien Franchet (Wellcome Open Research)
Background The aryl hydrocarbon receptor (AHR) plays important roles in intestinal homeostasis, limiting tumour growth and promoting differentiation in the intestinal epithelium. Spineless, the Drosophila homolog of AHR, has only been studied in the context of development but not in the adult intestine. Methods The role of Spineless in the Drosophila midgut was studied by overexpression or inactivation of Spineless in infection and tumour models and RNA sequencing of sorted midgut progenitor cells. Results We show that spineless is upregulated in the adult intestinal epithelium after infection with Pseudomonas entomophila (P.e.). Spineless inactivation increased stem cell proliferation following infection-induced injury. Spineless overexpression limited intestinal stem cell proliferation and reduced survival after infection. In two tumour models, using either Notch RNAi or constitutively active Yorkie, Spineless suppressed tumour growth and doubled the lifespan of tumour-bearing flies. At the transcriptional level it reversed the gene expression changes induced in Yorkie tumours, counteracting cell proliferation and altered metabolism. Conclusions These findings demonstrate a new role for Spineless in the adult Drosophila midgut and highlight the evolutionarily conserved functions of AHR/Spineless in the control of proliferation and differentiation of the intestinal epithelium.